1998
DOI: 10.1143/jjap.37.3248
|View full text |Cite
|
Sign up to set email alerts
|

Near-Ohmic Contact of n-GaAs with GaS/GaAs Quasi-Metal-Insulator-Semiconductor Structure

Abstract: We report on the current-voltage (I–V) characteristics of a metal/ultrathin GaS (thickness<100 Å)/n+-GaAs (carrier concentration=2×1018 cm-3) quasi-metal-insulator-semiconductor (QMIS) structure. The GaS was grown by molecular beam epitaxy (MBE) employing the precursor tertiarybutyl-galliumsulfide-cubane ([(t-Bu)GaS]4). The I–V characteristics of the QMIS structure depend on the work function of various metals (Au, Al, Ti). We discovered that a QMIS structure leads to a reduction of Schottky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Work on GaS includes growth of GaS films and multilayers on a GaAs substrate, 8,10 thermal conductivity, 11 and fabrication of Ohmic contacts to n-GaAs using GaS. 9,12 Suhre et al 3 have shown that adding In to GaSe strengthens the material enough to polish optical faces along arbitrary crystalline directions while enhancing the optical characteristics.…”
Section: Ga 1−x Mnmentioning
confidence: 99%
“…Work on GaS includes growth of GaS films and multilayers on a GaAs substrate, 8,10 thermal conductivity, 11 and fabrication of Ohmic contacts to n-GaAs using GaS. 9,12 Suhre et al 3 have shown that adding In to GaSe strengthens the material enough to polish optical faces along arbitrary crystalline directions while enhancing the optical characteristics.…”
Section: Ga 1−x Mnmentioning
confidence: 99%
“…Direct deposition of GaS was successfully performed using a gallium cluster ([(t-Bu) GaS] 4 ) as a singlesource precursor under ultra-high vacuum conditions of the MBE system [102,103,112]. The substrates were cleaned using trisodium ethylaminoarsinic (TDMAAS) and bisdimethylaminochloroarsinic (BDMAASCl) [102].…”
Section: (D) Deposition Of Gasmentioning
confidence: 99%
“…The substrates were cleaned using trisodium ethylaminoarsinic (TDMAAS) and bisdimethylaminochloroarsinic (BDMAASCl) [102]. During the deposition of pure GaS, the precursor cell was maintained at 120 °C [102,112]. The substrate temperature was maintained in the 350 °C to 500 °C temperature range.…”
Section: (D) Deposition Of Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…By rearrangement of Ga and S atoms in the GaS, the films take the crystalline structure of the substrate [7,8]. This transformation can be used as the buffer layer especially in the GaAs semiconductor structures [11,12].…”
Section: Introductionmentioning
confidence: 99%